2010
DOI: 10.2174/187152710791292657
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Immune Response in the Pathogenesis of Amyotrophic Lateral Sclerosis: A Therapeutic Opportunity?

Abstract: The immune system has been found to be involved with positive and negative effects in the nervous system of amyotrophic lateral sclerosis (ALS) patients. In general, T cells, B cells, NK cells, mast cells, macrophages, dendritic cells, microglia, antibodies, complement and cytokines participate in limiting damage. Several mechanisms of action, such as production of neurotrophic growth factors and interaction with neurons and glial cells, have been shown to preserve these latter from injury and stimulate growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…3). This suggests a role for epigenetic regulation in molecular mechanisms known to drive sALS pathogenesis [16][18]. Furthermore, the identified DMGs included previously reported epigenetically regulated genes such as runt-related transcription factor 3 ( RUNX3 ), TNF-related apoptosis-inducing ligand ( TRAIL/TNFSF10 ), H19, neuritin 1 ( NRN1) and signal transducer and activator of transcription 5A ( STAT5A) [19][23], validating our approach.…”
Section: Resultssupporting
confidence: 75%
“…3). This suggests a role for epigenetic regulation in molecular mechanisms known to drive sALS pathogenesis [16][18]. Furthermore, the identified DMGs included previously reported epigenetically regulated genes such as runt-related transcription factor 3 ( RUNX3 ), TNF-related apoptosis-inducing ligand ( TRAIL/TNFSF10 ), H19, neuritin 1 ( NRN1) and signal transducer and activator of transcription 5A ( STAT5A) [19][23], validating our approach.…”
Section: Resultssupporting
confidence: 75%
“…Other immunomodulatory drugs have been tested in ALS 160,161 . A multicenter phase II/III RCT of masitinib (4.5 or 3 mg/kg/day) with concomitant riuzole given over 48 weeks has started.…”
Section: Ongoing or Planned Phase III Studiesmentioning
confidence: 99%
“…Inflammation is one of the aspects of the innate immune response. Interactions between innate immune system, brain and neurodegenerative diseases are known (Ghezzi et al, 1998;Gowing et al, 2006) and it has been reported that mast cells, macrophages, dendritic cells, microglia, complement and cytokines participate in limiting the damage (Calvo et al, 2010). Innate system was found activated in central and in peripheral system of ALS patients (Chandels et al, 2001;Elliott et al, 2001;Sta et al, 2011).…”
Section: Innate Immune Systemmentioning
confidence: 99%
“…Through such processes, microglia releases reactive oxygen species, proinflammatory cytokines, complement factors, and neurotoxic molecules, leading to further neuronal dysfunction and death (Heneka et al, 2011;Lasiene et al, 2011). In addition, the implication of the peripheral system and its participation in the cellular mechanisms that direct to neurodegeneration, as white blood cells, is well documented (Calvo et al, 2010;Ghezzi et al, 1998;Gowing et al, 2006). Many data from autoptic spinal cord and blood examinations of the ALS patients, animal and cellular models support an immune system involvement in ALS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%